Change of Return Wave Height in the Northwestern Pacific Ocean Associated with Global Warming Scenario - HATADA, Yoshio; YAMAGUCHI, Masataka; NONAKA, Hirokazu (PROCEEDINGS OF COASTAL ENGINEERING, JSCE, 2008)
Using 4 scenarios for the change of track or central pressure of typhoons associated with global warming, Monte-Carlo simulations are made of 1, 000 years of typhoons, including the typhoon-induced pressure (TIP) and typhoon-generated wave heights (TGWH), over the Northwestern Pacific Ocean. Then, 100-year return values and their confidence intervals of the TIP and the TGWH are estimated with an extreme value analysis. The conclusion is that the predicted probable change of 5 hPa and 0.5m of the return values in most sea areas around Japan are not significant in general but that changes exceeding 10 hPa and 1m may be expected in some areas such as offshore of Southern Japan.